Implantable cardioverter-defibrillators in arrhythmias: a rapid and systematic review of effectiveness. Issue 5 (1st May 2002) - Parkes, J; Bryant, J; Milne, R
Abstract : Objective: To review the effectiveness of implantable cardioverter-defibrillators (ICDs) in the management of risk factors for sudden cardiac death. Design: Systematic review of randomised controlled trials identified from searching eight electronic databases, bibliographies of relevant studies, and consulting experts. Main outcome measures: Absolute and relative reduction in mortality. Results: Seven trials met the inclusion criteria. These showed changes in absolute risk of total mortality ranging from +1.7% to −22.8% (relative risk reductions −7% to +54%). Estimated benefits from ICD treatment compared with conventional drug treatment at three years were 0.23 to 0.80 additional years of life. Conclusions: Evidence suggests that ICDs reduce total mortality in particular subgroups of patients at high risk of ventricular arrhythmias. The optimal strategy for identifying the patients who could benefit most is not clearly established. Ongoing trials into the treatment of cardiac failure with ICDs may provide further evidence about subgroups in whom ICDs are most cost effective.